The Impact of the Implementation of Law No. 22 of 2009 on the Ownership of Individual Vehicle Driver's License at the Langkat Police - Sembiring, Deni Christo; Isnaini, Isnaini; Pinem, Serimin (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the impact of the implementation of Law No. 22 of 2009 concerning Road Traffic and Transportation on the ownership of individual vehicle Driver's License (SIM) in the jurisdiction of the Langkat Police. The method used in this study is a qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results of the study show that although these regulations have been implemented effectively with the existence of Mobile SIM services and online registration systems, there are still some obstacles. Among them are difficulties in practical exams, low legal awareness of the community, and the rampant practice of fraud in the process of making driver's licenses. In addition, the limited practical exam facilities and the number of supervisory personnel are also obstacles in the implementation of this regulation. This research suggests the need to increase public education, improve SIM service infrastructure, and increase law enforcement to reduce violations and increase public compliance with traffic regulations. It is hoped that with this improvement, driver's license ownership in the Langkat Police area can increase, and the number of traffic accidents can be reduced.